2010
DOI: 10.4314/ajbr.v4i3.53907
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cobalt, manganese and iron in the skin and hair of West African dwarf sheep and goats in Nigeria

Abstract: The distribution of cobalt (Co), manganese (Mn) and iron (Fe) was investigated in the skin and hair of 16 West African Dwarf sheep and goats. All three trace elements were present in varying amounts in both tissues. There were, however, some regional intraand interspecies differences Some of these differences were found to be statistically significant. These findings are discussed with reference to their possible implications for cutaneous manifestation of deficiency and other disease syndromes in the animals. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Nugroho (2008) states that Mn functions as carbohydrate synthesis, mucopolysaccharide, and enzyme systems, such as pyruvate carboxylase and arginine synthetase. In addition to enzymatic reactions, Mn also functions for growth and reproduction of livestock, Onwuka et al (2001) which states that Mn's mineral content in goats ranges from 2.98-13.9 mg/dl. Based on these data, it can be concluded that the livestock reared with A. marina leaf-based feed does not experience Mn mineral deficiency because the Mn content in the forage is sufficient.…”
Section: Macro and Micro Mineral Contentsmentioning
confidence: 99%
“…Nugroho (2008) states that Mn functions as carbohydrate synthesis, mucopolysaccharide, and enzyme systems, such as pyruvate carboxylase and arginine synthetase. In addition to enzymatic reactions, Mn also functions for growth and reproduction of livestock, Onwuka et al (2001) which states that Mn's mineral content in goats ranges from 2.98-13.9 mg/dl. Based on these data, it can be concluded that the livestock reared with A. marina leaf-based feed does not experience Mn mineral deficiency because the Mn content in the forage is sufficient.…”
Section: Macro and Micro Mineral Contentsmentioning
confidence: 99%
“…This assumption is supported by a recent report on the higher density of collagen fibrils in calf and goat parchments, compared with a more open weave and higher fat content in sheep parchments (Fiddyment et al, 2015). Other differences between the animal species could also contribute to the distinction in MEES results (Onwuka et al, 2001).…”
Section: Resultsmentioning
confidence: 99%